Neonatal parenteral nutrition: Review of the pharmacist role as a prescriber - Ragab, Mohamed H. (Saudi Pharm J, 2016)
INTRODUCTION: In the context of the continuous quest to improve the care of the neonates especially the critically ill premature infants, the extended role of pharmacists in the process of parenteral nutrition order writing and effective participation in decision-making especially in the neonatal population is increasingly important. This review aims to present results from the literature review of available evidence on the pharmacist role in neonatal parenteral nutrition therapy. MATERIAL AND METHODS: Key medical, clinical, and review databases were searched; relevant articles were retrieved and evaluated. RESULTS AND DISCUSSION: A total of 19 papers out of 7127 searched papers met the criteria for inclusion, discussing the review topic. The main focus of the selected papers was on parenteral nutrition practice as related to the pharmacy practice. The overall quality of studies was mixed. CONCLUSION: Overall, the review presents the up-to-date status of the most recent analysis being undertaken on the topic of pharmacist involvement in the parenteral nutrition order writing practices and more specific in the neonatal population over the period from 1979 to 2013. The overall impression is that the practice of pharmacist writing neonatal parenteral nutrition orders already exists, but still limited if compared with the practice of pharmacist writing adult parenteral nutrition orders which is much more established in many countries. There was no single clinical study evaluating this practice, as we were able to retrieve only two surveys, which make it difficult to evaluate the pharmacist role in this area. Nevertheless, despite the wide variation in literature types, characteristics and quality, there are consistent patterns across all the reviewed literatures that competencies of the pharmacist in this field are well represented, which make it very important to carry out good quality clinical studies in this field. Finally, we are currently conducting a prospective clinical study to evaluate the impact of clinical pharmacist as a neonatal PN prescriber, this impact will be judged through the study outcomes as reducing the metabolic and electrolyte complications and increasing the mean daily weight gain during PN therapy and reducing the average number of days of PN till enteral feeding is achieved.